2012
DOI: 10.1099/jmm.0.049726-0
|View full text |Cite
|
Sign up to set email alerts
|

Regional outbreak of CTX-M-2 β-lactamase-producing Proteus mirabilis in Japan

Abstract: Proteus mirabilis is a common cause of urinary tract infection. Wild-type P. mirabilis strains are usually susceptible to penicillins and cephalosporins, but occurrences of P. mirabilis producing extended-spectrum b-lactamases (ESBLs) have been recently reported. Here, we surveyed the prevalence of cefotaxime resistance among P. mirabilis strains at seven different hospitals in Kanagawa Prefecture, Japan, and investigated their molecular epidemiology to explain the mechanism of their spread. The prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
(58 reference statements)
1
20
1
Order By: Relevance
“…These infectious diseases are a threat to human health, and indeed, outbreaks and serious clinical cases have occurred [17]. Effective disinfection of healthcare equipment and surfaces is critical for preventing transmission of potential pathogens [18].…”
Section: Introductionmentioning
confidence: 99%
“…These infectious diseases are a threat to human health, and indeed, outbreaks and serious clinical cases have occurred [17]. Effective disinfection of healthcare equipment and surfaces is critical for preventing transmission of potential pathogens [18].…”
Section: Introductionmentioning
confidence: 99%
“…CTX-M-2 was identified in Argentina in 1989, first in different Salmonella serovars and then in diverse species of Enterobacteriaceae (1). Although it is not observed as frequently as CTX-M-1-and CTX-M-9-group enzymes, CTX-M-2 is endemic in South America (1,6), caused a regional outbreak in Japan (7), circulates in animal and human strains in some European countries (8), and has been reported in North America (4,5). In South America and Europe, bla CTX-M-2 is associated mainly with complex sul1-type integrons containing ISCR1 (9,10), while in Japan most cases are associated with ISEcp1 (7,11).…”
mentioning
confidence: 99%
“…In South America and Europe, bla CTX-M-2 is associated mainly with complex sul1-type integrons containing ISCR1 (9,10), while in Japan most cases are associated with ISEcp1 (7,11). Only a few studies have examined the incompatibility (Inc) types of the plasmids carrying bla CTX-M-2 (7,8,11,12). In a survey of human and poultry isolates from Europe, bla CTX-M genes were found to be associated with IncHI2-type plasmids, and all bla CTX-M-2 -carrying plasmids belonged to the IncHI2 APEC-O1-R type (8,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These organisms are one of the main causes of infections such as UTI (urinary tract infection), respiratory tract, wounds, bacteremia and other opportunistic infections and perhaps act as infection sources for extended-spectrum beta-lactamases (ES Ls) productions in both society and hospitals. Some studies have shown that the ES L and AmpC producing isolates of can be a cause of clonal spread in the hospital, regional and continent-wide outbreak (Nakano, 2012).…”
Section: Introductionmentioning
confidence: 99%